PREMATURE OVARIAN INSUFFICIENCY: MODERN VIEW OF THE PROBLEM - Елена Николаевна Кравченко; Мария Сергеевна Воронцова (The Publishing House Medicine and Enlightenment, 2022)
Premature ovarian insufficiency (POI) is an urgent problem that leads to persistent impairment of the quality of life, premature development of osteoporosis, cardiovascular diseases and persistent impairment of reproductive function (infertility). Due to polyetiology, today there is no universal method of prevention, and existing methods of treatment can only compensate for clinical symptoms, but cannot return reproductive function. Timely identification of at-risk patients, their joint management with narrow specialists (reproductive specialist, therapist, endocrinologist) can significantly improve the duration and quality of life of these women.